Co:BaTiO3/Sn:BaTiO3 Heterostructure Thin‐Film Capacitors with Ultrahigh Energy Density and Breakdown Strength - Je Oh Choi; Tae Yeon Kim; Seong Min Park; WooJun Seol; Hyunjin Joh; Gopinathan Anoop; Ji Young Jo (Advanced Electronic Materials, 2023)
Abstract Ferroelectric (FE) capacitors exhibiting ultrahigh power densities are widely utilized as electrostatic energy storage devices in pulsed electronic devices. One approach to maximize the discharge energy density (Ud) of capacitors is to increase the breakdown strength (Eb) accompanied with high maximum polarization (Pm) while suppressing the energy loss. However, the inverse relationship between Eb and Pm challenges the simultaneous enhancement of Eb and Ud. To overcome this limitation, FE/relaxor FE (RFE) heterostructure capacitors composed of Co‐doped BaTiO3 (BTCO) and Sn‐doped BaTiO3 (BTS) epitaxial thin film layers to decouple the Eb and Pm values are fabricated and the simultaneous enhancement of the Eb and Ud up to 7.9 MV cm−1 and 117 J cm−3, respectively is achieved. The high Eb and Ud values can be attributed to the suppression of the leakage current at the BTCO/BTS interface, a narrower hysteresis loop contributed by the BTS, and high Pm and Eb from the BTCO layer. Additionally, the BTCO/BTS heterostructure capacitors exhibit excellent fatigue endurance of up to 108 cycles and are thermal stable even at 160 °C. Through properly designing the FE and RFE layers, thermally stable and reliable FE/RFE heterostructure capacitors exhibiting high Ud and Eb can be realized.